Detection of the Vehicle Direction with Adaptive Threshold Algorithm Using Magnetic Sensor Nodes - Vancin, Sercan; Erdem, Ebubekir (Gazi Univ, 2018)
In this paper, we describe how, so as to perform vehicles direction detection in road traffic using proposed method along with the average-constant threshold and contributions of adaptive threshold detection algorithm (ATDA) thanks to special-purpose sensor nodes integrated with magnetic sensors. In this study, proposed algorithm with the adaptive threshold value as a magnetic resultant force has produced more pronounced and precise results than the average-fix threshold value. In this mean, it is clear that detected adaptive threshold generates more correct result for the systems like vehicle existence, direction assignment, and speed detection in different grounds where magnetic field is changeable as a result of environmental measurements. The direction of motion of the vehicles on the x-axis was determined as well as whether it was from left to right or from right to left, and the results were 97% average accurate. The simplicity of the proposed algorithms, the absence of any complex computations, the low cost of the sensor node and integration and the low power depletetion of the communication system show the avantage of this system in comparison with the other studies.
Keywords: Wireless sensor networks; magnetic sensor; adaptive threshold detection algorithm (ATDA); vehicle direction detection